PENYULUHAN TENTANG TANAMAN TOGA (RIMPANG TEMU HITAM) UNTUK MENURUNKAN KADAR GULA PADA PENYAKIT DIABETES DI DESA SIDODADI - Wahyudi Wahyudi; Angga Nugraha Sanjaya (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The trend back to nature is inseparable from the weakness of treatment using synthetic drugs (natural ingredients that are processed in a modern way). Some of them are side effects caused by the high cost of synthetic drugs that are not friendly to people with low economy, so knowledge about the use of medicinal plants is very important to have. knowledge about the toga (Intersection black rhizome) and the use of plants in the environment around the house that have medicinal properties are also lacking. The solution offered to overcome this problem is to provide education about the toga plant (Intersection black rhizome) and its health benefits in the form of: counseling to This counseling is carried out to increase the knowledge and skills of the Sidodadi village community in the use of toga (black ginger rhizome) for health, this activity is carried out by delivering material to the community and then conducting a rapid test so that the counseling takes place properly. both because of the covid 19 condition and the Q&A discussion in order to make the public understand and know the importance of the toga plant (Intersection black rhizome) for public health. An examination was also carried out before and after the testing of herbal medicines from the toga plant (Intersection black rhizome) this outreach program went well and the people of the village of Sidodadi were very enthusiastic in discussions or questions and answers. Medicinal plants planted in the yard can not only be consumed as an alternative choice for family medicine but can also be a source of additional income. In addition, these medicinal plants can also be a decoration that is pleasing to the eye when arranged beautifully. Family medicinal plants (TOGA) are essentially a plot of land in the yard used for medicinal plants in order to meet the family's need for medicines. about the use of toga as a family treatment seen from the increase in the average pretest score.